x2+6x-27=(x-3)

Subtract x from both sides of the equation.

x2+6x-27-x=-3

Subtract x from 6x.

x2+5x-27=-3

x2+5x-27=-3

Move 3 to the left side of the equation by adding it to both sides.

x2+5x-27+3=0

Add -27 and 3.

x2+5x-24=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -24 and whose sum is 5.

-3,8

Write the factored form using these integers.

(x-3)(x+8)=0

(x-3)(x+8)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-3=0

x+8=0

Set the first factor equal to 0.

x-3=0

Add 3 to both sides of the equation.

x=3

x=3

Set the next factor equal to 0.

x+8=0

Subtract 8 from both sides of the equation.

x=-8

x=-8

The final solution is all the values that make (x-3)(x+8)=0 true.

x=3,-8

Solve Using the Square Root Property x^2+6x-27=(x-3)